Некоторые вопросы образования и функционирования древнеанглийских долгих дифтонгов - Забулене, Л. (Kalbotyra, 1977)
The analysis of the formation of the long diphthongs /ēa ēo īo/ rests on the assumption that in early Primitive English they were biphonemic and bimoric, just like Proto-Germanic diphthongs. However, in historic and even in prehistoric periods of OE the reflexes of Proto-Germanic au, eu, iu should be treated already as monophonemes. Peculiar phonetic development of the elements of the diphthongs diverging from the corresponding monophonemes well attests to their monophonemic character.The analysis of the material leads to the conclusion that restrictions in the distribution of long diphthongs are closely connected with the conditions of their origin from old Germanic diphthongs and, on the other hand, with the character of the morphological system of OE.